Bioinspired Ultrasensitive Flexible Strain Sensors for Real-Time Wireless Detection of Liquid Leakage - Weilong Zhou; Yu Du; Yingying Chen; Congyuan Zhang; Xiaowei Ning; Heng Xie; Ting Wu; Jinlian Hu; Jinping Qu (Nano-Micro Letters)
Highlights Micro-extrusion compression molding and surface modification were proposed for the mass fabrication of a superhydrophobic thermoplastic polyurethane sensor (TCGS). Inspired by scorpions, TCGS features Archimedean spiral crack arrays and micropores, achieving 218.13 sensitivity at 2% strain, a 4300% increase, and over 5000 usage cycles of durability. The robust superhydrophobicity of TCGS improves sensitivity and stability for detecting small-scale liquid leakage, allowing precise monitoring across various sizes and compositions while providing early warnings in various scenarios.